TAYANGAN FILM TELEVISI (FTV) PERSPEKTIF PRODUKSI ORGANISASI - Robby Aditya Putra; Dede Mercy Rolando (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2018)
Solid teamwork in producing a television program is a necessity, so that production results are maximum and meaningful. If the production process is not carried out according to the plot, it will certainly have an impact on the program produced. Given the urgency, it is important to examine how the stages of production of the organization in making television films. This research focuses on the production of the organization (FTV) "Dzolim" on MNC TV. To dissect the case, the author uses the theory of production of the Branston and Stafford Organizations. This research shows that even though the production process of "Dzolim" FTV shows human resources, equipment and maximum costs, Dzolim's FTV content tends to be unnatural and too dramatizing